2013
DOI: 10.1503/cjs.020412
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a massive transfusion protocol (1:1:1) on major hepatic injuries: Does it increase abdominal wall closure rates?

Abstract: Background: Massive transfusion protocols (MTPs) using high plasma and platelet ratios for exsanguinating trauma patients are increasingly popular. Major liver injuries often require massive resuscitations and immediate hemorrhage control. Current published literature describes outcomes among patients with mixed patterns of injury. We sought to identify the effects of an MTP on patients with major liver trauma.Methods: Patients with grade 3, 4 or 5 liver injuries who required a massive blood component transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…22,23 The use of DCR during initial resuscitation has been associated with improved survival in the trauma population. 19,26 With the paradigm shift in resuscitation during the last decade and the frequency of liver injury, DCR's impact on severe liver injury should be explored. 16Y19,25 These studies have all evaluated the effect of DCR on the course of the injured patient, irrespective of type of injury.…”
mentioning
confidence: 99%
“…22,23 The use of DCR during initial resuscitation has been associated with improved survival in the trauma population. 19,26 With the paradigm shift in resuscitation during the last decade and the frequency of liver injury, DCR's impact on severe liver injury should be explored. 16Y19,25 These studies have all evaluated the effect of DCR on the course of the injured patient, irrespective of type of injury.…”
mentioning
confidence: 99%
“…The recently published reports ( 2011) showed the clear benefi ts of DCS on survival in injured patients who have been managed with DCR compared to conventional resuscitation methods [33].Also, the stay length in ICU has increasingly been reduced in patients requiring DCS and managed with DCR [30].DCR implementation in a specifi cally selected patient who required emergency surgery for trauma has signifi cantly decreased the need for DCS laparotomy and reduced mortality and increased the rate of defi nitive surgery at the fi rst operation in level 1 trauma centre [34]. The shift towards performing complete surgery was associated with signifi cant reductions in health care costs and resources utilization.Additionally, important studies reported higher rates of primary abdominal closure in the context of DCR approach [35,36].More recently and related to continued advances in trauma care, the DCR strategies have reduced the need for surgical haemostasis in severe liver trauma (>20%) by the direct address of trauma-induced coagulopathy, increased the rate of defi nitive surgery and reduced the need for DCS approach in a critically injured patient [37].…”
Section: History and Evolution Of Damage Control Surgery Conecptmentioning
confidence: 99%
“…The coincident evolution in resuscitation with hemostatic or balanced blood component resuscitation strategies [11][12][13][14] that limit use of crystalloid fluids are most probably also highly associated with a reduction in the prevalence of ACS (recognizing that excess crystalloid fluids are likely to be central in many cases of IAH/ACS) [15,16]. In support of these practices, a reduced incidence of open abdomens and ACS [17], and higher rates of abdominal closure with the adoption of damage control resuscitation and the use of negative pressure peritoneal therapy have been noted [18][19][20]. In 2017, the incidence of overt ACS is significantly lower than previous decades and may even been rare in some institutions.…”
Section: The Pastmentioning
confidence: 99%